Living under Economic Colonization: A Philosophical Remark on Arendt’s Human Condition - Ujan, Andre Ata (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
The culture of economic colonization is at the background and yet at the center of Arendt’s Human Condition. This colonizing culture is perfectly actualized through work and labor under a rhythmic coordination of a pater familias. It is more than ever enslaving and alienating, since it excludes possibilities for self-emancipation and provides no room for individuality. Work and labor therefore stand on the opposite side to the political. The culture they offer is in nature contradictory to the one promoted by the political. Hence the political is believed to be the remedy of economic and political problems. It in essence promotes action, i.e., the culture necessary for human self-emancipation. Arendt’s position on the idea of the political, however, must not be taken for granted. Arendt’s insistence on direct participation in political life has reminded us that citizens must be able to take care of their own desires and interests. It would be naïve to uncritically entrust one’s destiny, life, and future to the political authority or to the state.